2005
DOI: 10.1128/aem.71.11.6986-6997.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbial Community Compositions of Two Subglacial Environments Reveals a Possible Role for Microbes in Chemical Weathering Processes

Abstract: Viable microbes have been detected beneath several geographically distant glaciers underlain by different lithologies, but comparisons of their microbial communities have not previously been made. This study compared the microbial community compositions of samples from two glaciers overlying differing bedrock. Bulk meltwater chemistry indicates that sulfide oxidation and carbonate dissolution account for 90% of the solute flux from Bench Glacier, Alaska, whereas gypsum/anhydrite and carbonate dissolution accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
209
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(232 citation statements)
references
References 66 publications
19
209
3
1
Order By: Relevance
“…The nature of any chemolithotrophic processes present is dependent on the nature of electron donor/acceptor couples available for respiration, which in turn are dependent on the chemical properties of the subglacial environment [97]. A number of factors have been implicated in controlling subglacial chemistry.…”
Section: (E) Redox Chemistry and Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of any chemolithotrophic processes present is dependent on the nature of electron donor/acceptor couples available for respiration, which in turn are dependent on the chemical properties of the subglacial environment [97]. A number of factors have been implicated in controlling subglacial chemistry.…”
Section: (E) Redox Chemistry and Thermodynamicsmentioning
confidence: 99%
“…Early findings suggested that meltwater inputs controlled the amount of oxygen entering some subglacial systems and, consequently, their redox state [74]. Other studies pointed to bedrock composition as being influential in governing microbial communities by providing mineral and carbon substrates [96,97]. As the fourth most abundant element in the lithosphere, iron is likely to have a critical role in the redox chemistry of many subglacial water masses.…”
Section: (E) Redox Chemistry and Thermodynamicsmentioning
confidence: 99%
“…Comparative sequence analysis of the 16S rRNA genes revealed a high level of sequence identity between the new nitrite oxidizing betaproteobacterium and clone Run-S67 (AB247475) from domestic sewage (99.0%), clone Elb 168 (AJ421928) from a biofilm of a polluted river (98.8%) (Brü mmer et al, 2003), clone BG.g12 (DQ228379) from subglacial environments (97.8%) (Skidmore et al, 2005) and clone c5LKS43 (AM086129) from sediments of the mesotrophic lake Kinneret (96.3%) (Schwarz et al, 2007). The next related taxonomically described organism is Gallionella ferruginea (93.5% similarity).…”
Section: S Rrna Gene Sequence and Phylogenetic Analysismentioning
confidence: 99%
“…Microbial activity was also found in ice sediments of perennial and permanent lake ice [5,6] and in the Antarctic Sea [7,8]. Anaerobic microorganisms were isolated from glacier samples in the Arctic [9,10] and Greenland [11]. …”
Section: Introductionmentioning
confidence: 99%